2023
DOI: 10.22323/2.22020201
|View full text |Cite
|
Sign up to set email alerts
|

Citizen science and participatory science communication: an empirically informed discussion connecting research and theory

Abstract: Citizen Science is believed to contribute significantly to the democratisation of science, engaging non-scientists in scientific research. Participatory approaches to science communication share the same interest through public participation and public engagement. In the attempt to connect these two debates both theoretically and empirically, we provide an analysis of the communication tools and strategies used by 157 Citizen Science projects across the EU, UK, and Switzerland. Our analysis reports that the CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Criticism about the configuration (Mackenzie, 2006) of online users through protocols (Van Dijck, 2013) as well as accusations about exploiting unpaid labour through platforms (Gandini, 2021) apply also in the case of Citizen Science platforms and related online portals; Mahr and Dickel (2019) critically consider how data collection by non-experts is actually a sort of unpaid labour with some consequences, undermining the promises for democratisation and opportunities for the openness of technoscience (Mirowski, 2018). Also international surveys reported how main activity for non-experts invited to join Citizen Science project consist in accomplishing tasks for data collection, often through dedicated apps (Giardullo et al, 2023;Hecker et al, 2018) Although they enable processes of participation under certain conditions, ICTs can be part of a reiterated distancing between experts and non-experts. Most recent research on Citizen Science digital platforms has dealt with the use of data collected by non-experts (Giardullo, 2022;Ponti et al, 2022): many Citizen Science platforms use data to train machine learning algorithms for automated classification of data.…”
Section: (P 225)mentioning
confidence: 99%
See 1 more Smart Citation
“…Criticism about the configuration (Mackenzie, 2006) of online users through protocols (Van Dijck, 2013) as well as accusations about exploiting unpaid labour through platforms (Gandini, 2021) apply also in the case of Citizen Science platforms and related online portals; Mahr and Dickel (2019) critically consider how data collection by non-experts is actually a sort of unpaid labour with some consequences, undermining the promises for democratisation and opportunities for the openness of technoscience (Mirowski, 2018). Also international surveys reported how main activity for non-experts invited to join Citizen Science project consist in accomplishing tasks for data collection, often through dedicated apps (Giardullo et al, 2023;Hecker et al, 2018) Although they enable processes of participation under certain conditions, ICTs can be part of a reiterated distancing between experts and non-experts. Most recent research on Citizen Science digital platforms has dealt with the use of data collected by non-experts (Giardullo, 2022;Ponti et al, 2022): many Citizen Science platforms use data to train machine learning algorithms for automated classification of data.…”
Section: (P 225)mentioning
confidence: 99%
“…How to cite this article: Giardullo, P. (2023). Non-experts' participation in processes of scientific knowledge creation: The case of Citizen Science.…”
Section: Author Biographymentioning
confidence: 99%
“…This led to more than 2,000 media reports throughout the lifetime of the program, including newspaper articles, online articles, radio features and contributions on national television channels (however, due to a lack of data of these media reports we were unable to evaluate the success of these measures in regards to recruiting participants). A study by Giardullo et al (2023) has shown that 85.3 % of citizen science projects surveyed in the EU, United Kingdom and Switzerland used social media as communication medium for their projects, indicating the importance of digital communication tools to reach large target groups (Giardullo et al, 2023).…”
Section: Phase 1: Communication To Recruit and Motivate A Sufficient ...mentioning
confidence: 99%
“…In this sense, CS offers great potential for science communication, because in CS projects research and communication are not separate processes, but closely intertwined (Wagenknecht et al, 2021). Through interactions between scientists and citizens, the target audience essentially becomes involved in the communication process itself (Giardullo et al, 2023), thus moving communication beyond mere dissemination of project results (Gascoigne et al, 2022).…”
Section: Introductionmentioning
confidence: 99%